2006
DOI: 10.1111/j.1365-2516.2006.01400.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different inhibitor reactivities with commercial factor VIII concentrates on thrombin generation

Abstract: In order to describe the haemostatic role of a variation in inhibitor reactivity with different factor VIII (FVIII) concentrates, we have compared inhibitor titres against a panel of FVIII concentrates and correlated titre with the capacity to inhibit thrombin generation. Three plasma-derived concentrates were tested in vitro in mixing experiments with inhibitor plasmas from 11 patients with severe haemophilia A: Fanhdi, which contains von Willebrand factor (VWF) with a final ratio of approximately 1:1 (VWF IU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 23 publications
2
50
0
Order By: Relevance
“…ITI is the only proven therapy for inhibitors, but puts enormous challenges on patients and the community in terms of venous access and economic burden (up to 1 million Euros), so that it is prohibitive for many countries. After several in vitro studies showed a decrease in inhibitor activity against FVIII complexed with VWF (VWF/FVIII) compared with that against recombinant FVIII [39,40], a number of clinical studies have explored the role of FVIII source in ITI, and some clinical experience in Europe and the USA suggest that plasma-derived FVIII products rich in VWF may increase the likelihood of successful ITI [41]. In this context, the results of two large ongoing prospective randomized trials, the Rescue Immune Tolerance Study (RESIST)-naive (ITI-naive patients with poor prognostic factors are randomly assigned to VWF/FVIII or recombinant FVIII at a dose of 200 IU/kg/day) and RESIST-experienced (patients who have previously failed ITI with monoclonal or recombinant FVIII undergo ITI using VWF/FVIII containing plasma-derived concentrates at a daily dose of 200 IU/kg), will perhaps help us to elucidate the role of FVIII source in ITI [42].…”
Section: Treatment Of Hemophilia: the Presentmentioning
confidence: 99%
“…ITI is the only proven therapy for inhibitors, but puts enormous challenges on patients and the community in terms of venous access and economic burden (up to 1 million Euros), so that it is prohibitive for many countries. After several in vitro studies showed a decrease in inhibitor activity against FVIII complexed with VWF (VWF/FVIII) compared with that against recombinant FVIII [39,40], a number of clinical studies have explored the role of FVIII source in ITI, and some clinical experience in Europe and the USA suggest that plasma-derived FVIII products rich in VWF may increase the likelihood of successful ITI [41]. In this context, the results of two large ongoing prospective randomized trials, the Rescue Immune Tolerance Study (RESIST)-naive (ITI-naive patients with poor prognostic factors are randomly assigned to VWF/FVIII or recombinant FVIII at a dose of 200 IU/kg/day) and RESIST-experienced (patients who have previously failed ITI with monoclonal or recombinant FVIII undergo ITI using VWF/FVIII containing plasma-derived concentrates at a daily dose of 200 IU/kg), will perhaps help us to elucidate the role of FVIII source in ITI [42].…”
Section: Treatment Of Hemophilia: the Presentmentioning
confidence: 99%
“…82,83 Accordingly, the participants of the International Workshop on Immune Tolerance Induction declared by consensus that FVIII products with and without VWF may be used for ITI, but that after failure with rFVIII, switching to a VWFcontaining pdFVIII product should be considered (evidence level IIB). 91 At the functional level, in vitro experiments have shown that VWF dose-dependently interferes with the neutralizing effect of light chain-specific inhibitors on rFVIII:C. 64,[92][93][94] Shi and colleagues provided both in vitro and in vivo evidence that rFVIII in a preformed complex with VWF (rFVIII-VWF) is better protected from the inactivation by inhibitors than rFVIII that encounters inhibitors and VWF at the same time. In particular, when 'naked' rFVIII was mixed with murine plasma containing VWF and inhibitors, the normalized apparent Bethesda titers (as a measure of FVIII inactivation) were 5.8-fold lower compared to VWF-free control mixtures.…”
mentioning
confidence: 99%
“…There is a reasonable biological explanation for this, as the proteolysis of A1 and A2 domains of activated BDD-rFVIII proceeded up to 13 times faster than that of pd-FVIII or full-length rFVIII [9]. Thrombin generation studies also support this finding, as pd-FVIII products added to FVIIIdeficient plasma with the presence of inhibitor generate more thrombin than do rFVIIIs, which usually lacks von Willebrand factor (VWF) [21]. It is also noteworthy that patients treated with a single pd-FVIII product had a lower cumulative incidence of inhibitors (0-12%) than those treated with a single rFVIII (36-39%), independent of disease severity, study size or inhibitor testing frequency [22].…”
mentioning
confidence: 68%
“…Therefore, an alternative strategy might be identified to overcome these remarkable discrepancies among laboratories and different assay methods for measuring FVIII in haemophilic plasmas after infusion of concentrates. The analysis of parameters of thrombin generation or the clot waveform analysis or both may reveal as useful techniques not only to explore a bleeding tendency but also for monitoring patients in gene and replacement therapy [18,21,[23][24][25][26]. Fluorogenic thrombin generation assays have optimal sensitivity, less than 1% FVIII, and acceptable intralaboratory variation [25,26].…”
mentioning
confidence: 99%